Pelatihan Entrepreneur Madu Herbal Anugerah Sukses Berkah Internasional (ASBI): Meningkatkan Keterampilan Bisnis Madu Lokal untuk Pemberdayaan Masyarakat - Nurjanah, Siti; Zulaikha, Siti; Budi Prasetiyono, Agung; Abidin, Zainal; Ismail, Habib; Iwannudin, Iwannudin; Arsyad, Mufid (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
The Entrepreneur Training for Anugrah Sukses Berkah Internasional (ASBI) Honey aims to enhance the entrepreneurial skills of the community in managing and developing local honey businesses, particularly pure honey and pure honey with herbal additives. This event was held on February 8, 2025, at the ASBI PT. Auditorium, Metro City, Lampung, with 100 participants from various regions in Lampung. The training featured three expert speakers: Zainal Abidin, the owner of PT. ASBI, who presented the company's profile and strategies for developing ASBI honey business; Ari Suponto, a marketing expert, who explained marketing techniques and product development for ASBI honey; and Habib Ismail, an entrepreneurship practitioner, who shared insights on the importance of an entrepreneurial mindset in managing a business. The method used in this community service is an approach that combines training, education, and mentoring, aimed at providing practical understanding to participants on essential aspects of developing a honey business. Through these training sessions, participants were taught the importance of digital marketing, sound financial management, and product development to increase competitiveness in the market. The outcome of this training is expected to empower the community to professionally and sustainably develop the ASBI honey business while expanding the local honey product market network at the national level.